Os museólogos e a gestão do patrimônio cultural: a atuação dos museólogos em projetos de musealização ou patrimonialização de bens culturais - Igor Cândido Costa (2023)
This dissertation aims to present an exploratory study about the potentialities of museologists to perform on cultural heritage field out of museum establishments, in Minas Gerais State, Brazil. Brings to context museologists as musealization and patrimonialization agent through bibliographic review and exhibits results of qualitative study carried out by semistructured interviews among seven museologists who had act on cultural heritage management projects on that state. After theoretical reviews and research field, it concludes that the museologist has relevant potential to act as a mediator agent in projects that enhance and preserve people’s cultural heritage, by incorporating subjectivity and individuality of social actors on those processes.